Regional development disparities and their connection with hidden economy - Blagica Novkovska (UTMS Journal of Economics, 2017)
Regional disparities in the development of regions of a country may slow the growth of the entire national economy. Determination of such disparities is required for the creation of proper economic policies, needed to take actions against factors hindering economic growth. Hidden economy is, on the other, a phenomenon reflecting various weaknesses of the economy related to similar factors as those affecting regional development. In this paper we discuss the issue of connection between the regional disparities and the evolution of hidden economy in the considered regions. Development indices for eight regions of the Republic of Macedonia have been determined for the period 2008-2015. Economic, demographic and (total) development indices are calculated using economic (GDP per capita, unemployment rate, etc.) and demographic indicators (natural population growth, net migration rate, etc.) and rankings by level of development for different sub-periods are displayed. Three out of eight regions performed substantially weaker than the national average, one region performed substantially better than the average, and the rest performed close to the national average. Close link with the evolution of hidden economy for the considered regions is observed, indicating that the disparities and hidden economy are connected. Therefore, economic policies dealing with regional development and hidden economy must be coordinated to obtain maximum results for regions and the whole country.
Keywords: E26; R11; R58; 330; Economic development; Economic index; Development index